Preparation and Characterization of Cellulose Membrane Modified with β-Cyclodextrin for Chiral Separation - Ji, Yibing; Ke, Jian; Duan, Feifei; Chen, Jianqiu (Journal of Membrane and Separation Technology, 2016)
In this study, it is first time to obtain a complete separation of using β-cyclodextrin (β-CD) modified cellulose microfiltration membrane. Commercially cellulose membrane with the pore diameter of 0.22μm was functionalized with β-cyclodextrin (β-CD) by aldolization at the solid–liquid interface. Filtration experiments were carried out using a dead-end filtration cell holding a flat sheet membrane with effective area of 36 mm2. Aqueous solution of racemic tryptophan (0.05g/L, 150 mL) was forced to permeate through the cellulose membrane immobilized by β-CD at a flow rate of 0.1 ml/min through the membrane microdevice. Chiral ligand exchange chromatography was used to determine the concentration and ratio of D- and L-tryptophan in the filtrate. A complete separation of racemic tryptophan can be obtained by using this novel composite membrane-based separation system. In addition, a multi-stage filtration separation was applied in order to obtain higher permselectivity. The objective of this study is to obtain an easy prepared chiral membrane with good reproducibility and can be applied to a variety of chiral separations.